Unimodal sized silica nanocapsules produced through water-in-oil emulsions prepared by sequential irradiation of kilo- and submega-hertz ultrasounds. Issue 37 (29th June 2021) - Nemoto, Takahiro; Sakai, Toshio; Okada, Tomohiko
Abstract : Silica nanocapsules were prepared using water droplets dispersed in soybean oil via sequential ultrasound irradiation (28 kHz → 200 kHz → 950 kHz). Abstract : This study investigates the regulation of the size of 100 nm hollow-sphere silica particles using surfactant-free water-in-oil (W/O) emulsion. First, water droplets were dispersed in soybean oil via sequential ultrasound irradiation (28 kHz → 200 kHz → 950 kHz). A precursor of hollow silica particles was prepared using hydrolysis and polymerization of methylsilyl trichloride into a stable W/O emulsion. The final structure/morphology of the silica particles was influenced by the volume ratio of water/soybean oil, the cycle number of the sequential ultrasound irradiation, and the amount of organosilane added to the emulsion. The emulsion was stabilized by Ostwald ripening, as the size distribution at 5/10 3 (water/oil = v/v) was a bimodal split between a water droplet size of a few μm and some with a size of a few tens of nm. The most appropriate cycle number was 3 in this system. Further cycling to 5 resulted in a broad and bimodal size distribution of the final particles due to rapid coalescence of water droplets. Subsequent hydrolysis of methylsilyl trichloride consumed water with diminishing large droplets, forming fine and unimodal (0.12 ± 0.02 μm) hollow silica particles. Very fine and uniform-sized hollow particles (0.08 ± 0.01 μm) were successfully produced by decreasing the volume ratio to 1/10 3 (water/oil) because of a transparent stable emulsion as a homogeneous template of the hollow structures.